Empirical Study of Magnet Distance on Magneto-Mechanical Resonance Frequency - Knopp Tobias; Mohn Fabian; Foerger Fynn; Thieben Florian; Hackelberg Niklas; Faltinath Jonas; Tsanda Artyom; Boberg Marija; Möddel Martin (Current Directions in Biomedical Engineering)
Determining the position and orientation of a medical instrument is essential for accurate procedures in endoscopy, surgery, and vascular interventions. Recently, a novel sensor based on torsional pendulum-like magneto-mechanical motion has been proposed. This sensor is passive, wireless and inductively coupled to a transmit-receive coil array. This setup allows the determination of all 6 degrees of freedom using the characteristic resonance of the sensor. Additional physical quantities such as temperature and pressure can be measured based on the frequency of the sensor, which mainly depends on the distance between the two involved permanent magnets. In this study, we analyze a sensor composed of two magnetic cylinders with variable magnet-to-magnet distance and a basic physical model based on a dipole assumption. Experimental analysis of the resonance frequency and comparison with the model values show both qualitative and quantitative agreement with an average relative error of only 0.8 %. This validates the implemented model and shows the suitability of our magneticmechanical resonator made from cylindrical permanent magnets for sensing applications.